2018
DOI: 10.1038/s41598-018-20651-3
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention versus Coronary Artery Bypass Graft in Acute Coronary Syndrome patients with Renal Dysfunction

Abstract: ACS patients with renal dysfunction tend to have a poorer prognosis than those with normal renal function. This retrospective cohort study was performed using The Second Drug-Eluting Stent Impact on Revascularization Registry, a retrospective registry, to evaluate the time-dependent relative risk of revascularization strategies in ACS patients with renal dysfunction. The study demonstrated that the short-term MACCE rate was lower after PCI than CABG. However, there was no significant difference in long-term MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Symptomatic patients with significant CAD that affect their quality of life are considered for PCI [ 13 ]. Comorbidities, including heart failure, renal impairment, and advanced age, are evaluated to assess procedural risk and guide treatment decisions [ 14 , 15 ]. The anatomical complexity of coronary lesions, including factors like severe calcification or bifurcation disease, along with the presence of left main or multivessel disease influences the need for revascularization and choice between PCI and CABG [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…Symptomatic patients with significant CAD that affect their quality of life are considered for PCI [ 13 ]. Comorbidities, including heart failure, renal impairment, and advanced age, are evaluated to assess procedural risk and guide treatment decisions [ 14 , 15 ]. The anatomical complexity of coronary lesions, including factors like severe calcification or bifurcation disease, along with the presence of left main or multivessel disease influences the need for revascularization and choice between PCI and CABG [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
“…The majority of these studies designated MACCE as the primary outcome and concluded CABG is associated with fewer adverse events in patients with CKD than in PCI (14,15). However, some studies have published contrary findings (16,17), most likely due to differences in the stent type and definitions of the primary outcome. Therefore, we sought to better clarify the risk of PCI in the current-generation drug-eluting stenting and compare it with that of CABG.…”
Section: Cardiovascular Adverse Eventsmentioning
confidence: 99%
“…Several meta-analyses have evaluated revascularization techniques in patients with renal dysfunction, the results being inconsistent, because the majority of the trials were retrospective, with an increased degree of heterogeneity. There is a deficiency of randomized controlled trials that evaluated revascularization techniques for patients with ACS and renal dysfunction [142].…”
Section: Treatment Options Of Acs In Ckd Patientsmentioning
confidence: 99%